Pengaruh Model Pembelajaran Snowball Throwing Terhadap Minat Belajar Geografi Siswa SMA Negeri 2 Labuapi - Zaedun, Zaedun (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to describe the effect of the Snowball Throwing learning model on the learning interest of students at SMA Negeri 2 Labuapi in Geography. This research method using experiment. The research sample was taken from class XII IIS 1 as a control class consisting of 25 students and class XII IIS 2 as an experimental class of 27 students. The research instrument was a questionnaire of interest in learning geography which consisted of a pre-test and a post-test questionnaire. Based on the results of the study, there is a difference in interest between the experimental class that uses the snowball throwing learning model and the control class that uses lectures and questions and answers with sig (2-tailed) 0.000 <0.05, so that H0 is rejected and H1 is accepted, which means there is a difference in interest in learning geography. control class and experimental class. The average gain score for the experimental class was higher than that of the control class, namely 16.59> 3.08. This indicates that there is an effect of the snowball throwing learning model on the students' interest in learning geography in class XII SMA Negeri 2 Labuapi.